Neurological and psychiatric disorders in endocrine diseases - Gianluca Tamagno (Frontiers Research Topics, 2015)
Neurological and psychiatric disorders can occur in endocrine diseases either in the setting of the clinical manifestations of the same (i.e., hyper- or hyposecretion of hormones or peptides from the endocrine glands) or as events secondary to the pathogenetic mechanisms of the endocrinopathy (i.e., autommunity affecting endocrine glands and the brain). Also the medical or surgical treatment of the endocrine disease can sometimes determine the occurrence of neurological or psychiatric abnormalities. Moreover some genetic alterations can lead to syndromes affecting both the endocrine and the nervous system with a variety of possible manifestations. In the last couple of decades a number of associations between dysfunctions of the endocrine system and neurological or psychiatric manifestations have appeared and only in the minority of the cases this link has been fully elucidated. Often the neurological or psychiatric alterations still represent a relevant challenge for clinicians with regard to the management of the patients. The complexity of the topic and the limited availability of laboratory research models for the study of the endocrine system-nervous system cross-interaction are making the scientific progresses intricate and, sometimes, slow. A dedicated focus to such broad and often still obscure topic might help and clarify the current state-of-the-art in the field and direct the goals of future research.